A Non‐Perilous Coumarin‐Based Ratiometric Probe for ′In Vitro′ Detection of Cu through Cell Imaging Technique. Issue 27 (21st September 2017) - Kumari, Chanda; Sain, Dibyendu; Kumar, Ashish; Nayek, Hari Pada; Debnath, Sushanta; Saha, Partha; Dey, Swapan
Abstract: A novel coumarin based fluorescent turn on probe (R1 ) was designed and synthesized for 'on the spot' detection of biologically importantCu 2+ . The actual three dimensional geometry of the probe was confirmed by single crystal X‐ray analysis.R1 showed high sensitivity and selectivity towardsCu 2+ without any intervention of other metal ions. Rapid naked eye detection ofCu 2+ through colour change increased the superiority of the probe for practical use. Absorption and emission spectra proved the ratiometric detection ability of the probe towardsCu 2+ . Long wavelength visual fluorescence emission of the complex was utilized for intracellular detection ofCu 2+ in living cells. Abstract : A coumarin appended rhodamine probe (R1) was synthesized for the selective detection of Cu 2+ . The three dimensional structure of probe R1 was confirmed by solid state structure of R1. Probe R1 also showed its real time application to recognise Cu 2+ in live HeLa cell.